Florida Crop/Pest Management Profile: Lychee and Longan - Mark Mossler; O. Norman Nesheim (EDIS)
Revised! Circular 1400, a 9-page circular by Mark Mossler, profiles production of these tropical evergreen fruits in Florida, with production facts, cultural practices, and pest management.  Includes specialist contact information and references. Published by the UF Department of Horticultural Sciences, June 2009.